Whole Blood Expression of the Vascular Endothelial Growth Factor Family Relates to Cognitive Performance. (20th December 2022) - Libby, Julia B.; Seto, Mabel; Khan, Omair A.; Liu, Dandan; Petyuk, Vladislav A; Gifford, Katherine A.; Dumitrescu, Logan; Jefferson, Angela L.; Hohman, Timothy J.
Abstract: Background: The vascular endothelial growth factor ( VEGF ) family is involved in angiogenic signaling and has been implicated in Alzheimer's Disease (AD). Previous work from our team has found that higher transcript levels of VEGFB, PGF, FLT1, and FLT4 in the brain relate to worse cognitive performance and higher levels of AD neuropathology. This study explored whether comparable associations are observed when measuring mRNA in whole blood. Method: Transcriptomic, cognitive, and biomarker data were acquired from the Vanderbilt Memory & Aging Project. Participants (n=335) included older adults (age=72+/‐7.32) with normal cognition (n=203) or mild cognitive impairment (n=132). Expression of the ten genes in the VEGF family were quantified using RNA sequencing of blood. Outcomes included a composite measure of memory and cerebrospinal fluid (CSF) levels of β‐amyloid, total tau, and phosphorylated tau (ptau181). Linear regression models related VEGF family member expression to baseline cognitive performance and AD biomarkers. Linear mixed effects regression models assessed longitudinal change in cognition. All models covaried for age at baseline and sex. To aid in interpretation, Pearson correlations between blood and brain expression were calculated leveraging data from 137 participants from the Genotype Tissue Expression Project (GTexportal.org). Result: At baseline, higher levels of VEGFB mRNA were associated with better memory performance (Figure 1, β=0.47, p=0.008). In longitudinal analyses, higher baseline expression of PGF was associated with more rapid decline in memory (β= 0.02, p=0.04). No other significant associations were observed (p‐values>0.09). Among GTEx participants, higher expression of VEGFB in blood was correlated with lower expression in the brain (Figure 2, r=‐0.19, p=0.02). PGF correlations did not reach statistical significance (r=0.09, p=0.27). Conclusion: Higher PGF expression in blood relates to worse cognitive outcomes, consistent with previous findings in the brain. In contrast, higher levels of VEGFB in blood relates to better performance, opposite of the previously observed association in the brain. Notably, in GTEx we observed opposing correlations between blood levels of VEGFB and brain levels of VEGFB, suggesting that higher levels of VEGFB in the blood may indeed reflect lower levels in the brain. Our results highlight the potential of VEGFB and PGF as blood biomarkers in aging and AD.